Reviewing judicial review: constitutional and institutional competence / Jayanthi Naidu - Jayanthi, Naidu (2004)
This work examines the foundations of judicial review. By doing so, it explores the constitutional and institutional capacity of the reviewing court. The reason for this is that court decisions have infused new vigour into judicial review by moving it away from formalistic concerns of jurisdiction. Nevertheless the extent of such judicial enthusiasm is shrouded in controversy. Too often judgments are based on standards that transcend the particular case, leading to complex and even contradictory decisions. Further, it cannot be denied that principles are ignored and stare decisis is flouted towards the end of ''justice of the case". Any occasional judicial incursion into matters formally within the purview of the original decision-maker's realm is justified as a necessary and acceptable consequence of fulfilling this essential task. Further, changes in patterns of governance through privatization, contracting-out, selfregulation and the like have served to blur the traditional distinction between the public and private sphere. The cross fertilization gives rise to accountability concerns because otherwise, private actors can muscle their way into the traditional state machinery without much fanfare. This forwards serious questions in relation to rights enforcement and how judicial review can be invoked in the public-private interaction. These questions will continue to rage unless the foundational parameters are clarified. If the courts are constitutionally and institutionally competent, any controversies with regards its role will be extinguished. It will also be impetus towards developing a corpus of constitutional review, one that evolves with contemporary insight of the constitution. The focus is not whether the courts should decide all controversies or not, but how it can function as a mechanism of accountability in the interaction between the constitutional actors. This work concludes by showing that if the constitutional principles are clarified, then the constitutional actors will cease the current power play and instead work in partnership towards actualizing effective enjoyment of rights. The law is as at 30 April 2004.